PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. MABHAKTI (DHARMA BHAKTI MURTI) - I Putu Yuda Pratama; Putu Agus Eka Rismawan; Ary Wira Andika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Performance is the implementation of the plans that have been prepared. Performance implementation is carried out by human resources who have the ability, competence, motivation, and interests. This study aims to determine the effect of leadership style, motivation and work discipline on employee performance at PT. Mabhakti (Dharma Bhakti Murti). The population and sample in this study are all employees of PT. Mabhakti (Dharma Bhakti Murti) totaling 34 people. The sampling technique used in this study is the saturated sampling method or the census method. Data collection was carried out through observation, interviews, documentation, and questionnaires. The data analysis technique used in this study was multiple linear regression analysis which was processed using the SPSS version 25 program. Based on the results of the study it showed that leadership style had a significant positive effect on employee performance at PT. Mabhakti (Dharma Bhakti Murti). Motivation has a significant positive effect on employee performance at PT. Mabhakti (Dharma Bhakti Murti). Work discipline has a significant positive effect on employee performance at PT. Mabhakti (Dharma Bhakti Murti).